Determinants of safe sexual behavior of female sex workers in Tehran: the woman, her network, and the sexual partner - Zahra Jorjoran Shushtari; Yahya Salimi; Seyed Ali Hosseini; Homeira Sajjadi; Tom A. B. Snijders (BMC, 2021)
Abstract Background Despite the steady growth of sexual transmission of HIV, there is little evidence about safe sexual behavior of FSWs, and social network effects on this behavior, in Iran. Our aim in this study was to determine the effect of social network characteristics on condom use among FSWs, considering individual characteristics of the FSWs and of their sexual partners, characteristics of their relationship, and the FSW's personal network. Methods A cross-sectional ego-centric network survey of 170 FSWs was carried out in Tehran between January and June 2017. A multilevel ordered logistic regression analysis was conducted to examine the effects of individual and relational characteristics simultaneously. Results Condom use in sexual relationships of the FSWs on average was rather low. Important determinants of safe sexual behavior were found both at the level of the individual FSW and at the level of the sexual partner. The main determinants at the level of the individual FSW were FSWs' age and HIV knowledge. At the level of the sexual partner, age and education of sexual partners, as well as intimacy, duration of tie, frequency of contacts with a given partner, frequency of contact, perceived social support, and perceived safe sex norms were significantly associated with condom use. Conclusions The findings highlighted that considering only the individual characteristics of female sex workers is not sufficient for effectively promoting condom use. Factors at the network and dyadic level should also be considered, especially the role of sexual partners. Network-based interventions may be useful which modify social relationships to create a social environment that can facilitate changes in sexual behavior.